2021
DOI: 10.3390/molecules26092759
|View full text |Cite
|
Sign up to set email alerts
|

Lipase-Catalyzed Production of Sorbitol Laurate in a “2-in-1” Deep Eutectic System: Factors Affecting the Synthesis and Scalability

Abstract: Surfactants, such as glycolipids, are specialty compounds that can be encountered daily in cleaning agents, pharmaceuticals or even in food. Due to their wide range of applications and, more notably, their presence in hygiene products, the demand is continuously increasing worldwide. The established chemical synthesis of glycolipids presents several disadvantages, such as lack of specificity and selectivity. Moreover, the solubility of polyols, such as sugars or sugar alcohols, in organic solvents is rather lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 79 publications
0
29
0
Order By: Relevance
“…Enzymes require a minimal amount of water to maintain their hydration shell and stay active. This behavior observed is not singular to ß-glucosidases, indeed, lipases were also reported to exhibit the need for a minimum amount of water in a similar range of concentration (5-10 wt %) [33,36,40]. However, the investigated ß-glucosidases operate at relatively low water content compared to other glycosidic enzymes as for example, a-amylases required at least 10-20 % of water as co-solvent to show activity [20].…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Enzymes require a minimal amount of water to maintain their hydration shell and stay active. This behavior observed is not singular to ß-glucosidases, indeed, lipases were also reported to exhibit the need for a minimum amount of water in a similar range of concentration (5-10 wt %) [33,36,40]. However, the investigated ß-glucosidases operate at relatively low water content compared to other glycosidic enzymes as for example, a-amylases required at least 10-20 % of water as co-solvent to show activity [20].…”
Section: Discussionmentioning
confidence: 72%
“…Deep eutectic solvents (DES) that are made from inexpensive renewable raw materials [30] are an interesting alternative to organic solvents [25] or ionic liquids [26]. After the successful demonstration of various sugar synthons esterification with different fatty acid building blocks employing lipases in DES [39,40], whereby the sugar component can act as a solvent component and as a substrate at the same time [33,35,36,40], this study showed that glycosidases can also be used in DES for the synthesis of AGs according to the 2-in-1 concept. In other studies, presented so far, DES had mainly been used as a co-solvent [26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 20 Nonetheless, these compounds are of great interest in the food-, cosmetic-, and pharmaceutical industry. For example, sorbitol-6- O -laurate, a model compound studied by Delavault et al, 21 is structurally related to an emulsifier registered as E493, which is commonly employed for pharmaceutical and food applications and approved by the European Food Safety Authority (EFSA). 22 Enzymatic synthesis of glycolipids provides an alternative to chemical synthesis as milder conditions are applicable, for example, relatively low temperature, as well as selective synthesis, which reduces side product formation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the chemical procedure requires the use of harsh conditions like high temperature, acidic catalysis (e.g., by perfluorinated alkylsulfonic acid), and complicated processing requiring multiple steps of protection, deprotection, and activation (e.g., with allyl, benzyl, and p -methoxybenzyl groups), leading to wasteful side products. Nonetheless, these compounds are of great interest in the food-, cosmetic-, and pharmaceutical industry. For example, sorbitol-6- O -laurate, a model compound studied by Delavault et al, is structurally related to an emulsifier registered as E493, which is commonly employed for pharmaceutical and food applications and approved by the European Food Safety Authority (EFSA) . Enzymatic synthesis of glycolipids provides an alternative to chemical synthesis as milder conditions are applicable, for example, relatively low temperature, as well as selective synthesis, which reduces side product formation .…”
Section: Introductionmentioning
confidence: 99%